A latent class analysis of online victim-offender overlap among Chinese youth: examining overlap risks across online deviance types - Lin, Kai (Crime & delinquency, 2024)
This study aims to comprehensively test the applicability of lifestyle exposure theory (LET) against other criminogenic and victimogenic factors in predicting the differential risks of online offending-victimization overlap across multiple types of online deviance. Using self-reported survey data from 3,741 Chinese college students, the study performed Latent Class Analysis (LCA) and posterior multinomial logistic regression analysis. The LCA identified five latent classes of offending-victimization overlap, with only 6% of respondents reporting high overlap risk. Posterior multinomial logistic regression analysis showed that LET indicators and gender emerged as the most robust predictors of overlap risks compared to other theory-driven (e.g., control and routine activity theories) and sociodemographic factors. The current study accentuates the importance of methodological diversity in examining victim-offender overlap.